Corpus approaches to language, thought and communication - Lu, Wei-lun (Linguist); Kudrnáčová, Naděžda; Janda, Laura A. (Benjamins current topics ;, 2021)
"The studies in the present volume illustrate the current state-of-the-art in the corpus-based approach in cognitive linguistics, which seeks to motivate linguistic phenomena through the combination of quantitative and qualitative analysis. By focusing on language use in different contexts from a variety of perspectives, each of the contributions in this volume presents its own unique take on the intertwined relationship between language, thought, and communication. Thus, each article shows how a combination of quantitative and qualitative analytical techniques helps shed new light on old issues, reflecting the usage-based nature of cognitive linguistics and illustrating the explanatory adequacy of corpus-based methods. Originally published as special issue of Review of Cognitive Linguistics 17:1 (2019)"--